Potentiation of TNF-alpha toxicity by conjugation with ricin A-chain. - Gould, D; Foxwell, B; Feldmann, M; Chernajovsky, Y (1998)
Hybrid toxins containing a cytokine moiety have been used effectively to selectively kill cells expressing the complementary cytokine receptor both in vivo and in vitro. To date all cytokines incorporated into hybrid toxins, e.g. interleukin 2 are biologically active as monomers, so attachment of a toxin group causes minimal interference with the cytokine structure. By contrast, the pro-inflammatory and anti-cancer cytokine tumour necrosis factor alpha (TNF-alpha) is biologically active as a homotrimer in which the grooves created between the hydrophobically associated monomers form the receptor binding region, so maintenance of this structure is crucial for activity. In this report the authors show that TNF-alpha can be modified by reaction with a crosslinking agent and by subsequent attachment of the toxin ricin A-chain without loss of TNF-alpha cytotoxic activity in the WEHI assay. Structural association of the hybrid toxin composed of TNF-alpha and ricin A-chain was confirmed by Western blot analysis. The hybrid toxin was toxic to HeLa cells (IC50=4 pM) not sensitive to native TNF-alpha, and sensitive WEHI cells with substantially increased lethality (LD50=0.01 fM). This increased TNF-alpha cytotoxic activity suggests that hybrid toxins containing TNF-alpha may have therapeutic applications in the treatment of cancer.